2015
DOI: 10.1007/s00204-015-1548-z
|View full text |Cite
|
Sign up to set email alerts
|

Human metabolism and renal excretion of selenium compounds after oral ingestion of sodium selenite and selenized yeast dependent on the trimethylselenium ion (TMSe) status

Abstract: A human in vivo metabolism study was carried out to investigate the impact of the trimethylselenium ion (TMSe) status on metabolism and toxicokinetics of sodium selenite and selenized yeast. Nine healthy human volunteers were orally exposed to 200 µg selenium as sodium selenite and seven with selenized yeast (100 µg selenium). In each intervention group, three subjects belong to TMSe eliminators. Blood samples were withdrawn before and up to 6 h after administration. Urine samples were collected before and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Additionally, isotope 78 Se + ( m/z 78) shifting with oxygen to 78 Se 16 O + ( m/z 94) as well as both Se isotopes on mass were monitored in the same gas mode to screen for interferences. As a commonly used internal standard, Ge was detected on m/z 72 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, isotope 78 Se + ( m/z 78) shifting with oxygen to 78 Se 16 O + ( m/z 94) as well as both Se isotopes on mass were monitored in the same gas mode to screen for interferences. As a commonly used internal standard, Ge was detected on m/z 72 .…”
Section: Methodsmentioning
confidence: 99%
“…Se isotopes on mass were monitored in the same gas mode to screen for interferences. As a commonly used internal standard, Ge was detected on m/z 72[12,13].…”
mentioning
confidence: 99%
“…4A) than selenosugar 3, which is in agreement with the previously published data. 12,14 The selenosugar 1 and selenosugar 3 levels were clearly higher in the postsupplementation phase compared to the pre-supplementation phase ( Fig. 4A and B).…”
Section: Selenosugarsmentioning
confidence: 91%
“…12,13 Numerous studies explored the urinary excretion of selenium supplemented in various chemical forms, but based on different experimental designs employing single dosage administration. 12,[14][15][16] The aim of the present study is to investigate the urinary excretion of selenium metabolites in several volunteers following a regimen of a gradually increasing dosage of selenium supplementation to gain more insight into the human metabolism of selenium.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme produces a variety of products including the selenium analogue of TMS, the trimethylselenonium ion (TMSe), and possesses several key physiological and toxicological functions [3,4]. Several European studies have consistently reported considerable inter-individual variability (20–40 fold) in the human metabolism to TMSe, splitting the study populations into so-called “TMSe producers” and “TMSe non-producers” with a ratio of about 1:4 [57]. …”
Section: Introductionmentioning
confidence: 99%